ARVN : Life and Death in the South Vietnamese Army - Brigham, Robert K. (Robert Kendall), 1960- (Book collections on Project MUSE., 2006)
Along the way, he explodes some of the myths about ARVN soldiers' cowardice, corruption, and lack of patriotism that have made the ARVN the scapegoat for America's defeat." "Ultimately, as Brigham shows, without any real political commitment to a divided Vietnam or vision for the future, the ARVN retreated into a subnational culture that redefined the war's meaning: saving their families. His book gives us a fuller understanding not only of the Vietnam War but also of the problems associated with U.S. nation building through military intervention."--Jacket.